257 Situation analysis on child maltreatment prevention in Albania. (1st September 2016) - Qirjako, Gentiana; Pesevska, Dimitrinka Jordanova; Lazëri, Ledia; Sethi, Dinesh
Abstract : Background: Child maltreatment is a leading cause of health inequality and social injustice, with poorer and disadvantages populations being more in risk. The consequences of child abuse and exposure to different adverse childhood experiences in childhood both immediate and long-term consequences, have serious impact on physical, emotional well-being, development and health status of children. Method: During October 2015, a situation analysis on child maltreatment prevention in Albania was carried out, based on information gathered from relevant stakeholders in the country as well as on desk review of existing policy documents and reports. The aim of this analysis was to define the current situation of child maltreatment in Albania and take further actions for preventing in line with the recommendations of the European report on preventing child maltreatment and the WHO European child maltreatment prevention action plan 2015–2020. Results: Over the last decade, Albania has improved policy and legal framework for the protection of children's rights. On the other hand, the child maltreatment prevention and protection have been provided by the several relevant sectors: social, health, educational, police, justice and others. Non-governmental organisations take a part in providing services for children. Existing services are mainly focused on detection and protection of the victims, so further efforts should be done in development of the preventive programmes and evidence based practices tailored for the country context. Conclusions: Current policy and legal framework of the country enables suitable platform for child maltreatment prevention, but still there is a need for stronger policy and legal reinforcement and monitoring. A comprehensive action plan for the prevention of child maltreatment should be developed to significantly contribute in reducing the burden of child maltreatment and risk factors targeting prevention in Albania.